PENINGKATAN LITERASI DIGITAL DAN KEAMANAN DATA MELALUI PENYULUHAN KEPADA MASYARAKAT DESA MUNCANGELA, KABUPATEN KUNINGAN - Krisdiawan, Rio Andriyat; Husen, Dede; Asikin, Nida Amalia (Jurnal Abdi Insani, 2025)
Improving digital literacy and data security awareness has become essential amid the rise of hoaxes, phishing, and misuse of personal information in cyberspace. Rural communities, including Muncangela Village, often actively use social media without sufficient knowledge of digital security risks. This community service aimed to enhance digital literacy and data protection skills among residents of Muncangela Village, Kuningan Regency. The methods included an initial survey, case-based material design, interactive outreach, discussions, simulations, and evaluation through pre- and post-tests. Results indicated a significant increase in the cognitive dimension (+0.61), while attitudes and behaviors remained high. Self-efficacy and risk perception showed slight improvements. Training evaluation achieved an average score of 4.67, reflecting very high participant satisfaction. The program positively influenced participants’ awareness and understanding of data security practices and digital ethics. Continued mentoring is recommended to strengthen behavioral change and confidence in protecting personal data